Severe hyperlipidemia pancreatitis induced by taking tamoxifen after breast cancer surgery—Case report - Zhai, Chao; Li, Xiang; Xiao, Dong; Chen, Liang; Wang, Chaoyang; Zheng, MingHua (Frontiers in Oncology, 2023)
Introduction: The research investigates the mechanism, diagnosis, treatment, and subsequent endocrine therapy of severe pancreatitis induced by tamoxifen treatment in patients who had undergone breast cancer surgery. Case Presentation: We studied two cases of breast cancer in whom severe acute pancreatitis developed after taking tamoxifen for endocrine therapy in our hospital. Causes, clinical manifestations, treatment process and prognosis of severe acute pancreatitis were analyzed with a brief literature review provided. Both cases were patients with severe hyperlipidemia pancreatitis. After conservative treatment, none of them died. Pancreatitis did not recur after changing endocrine therapy drugs. Conclusion: Endocrine therapy with tamoxifen in breast cancer patients can induce hyperlipidemia, which can subsequently cause severe pancreatitis. The treatment of severe pancreatitis should strengthen the regulation of blood lipids. The application of low-molecular-weight heparin combined with insulin therapy can rapidly lower blood lipids. Involved treatments including acid suppression, enzyme suppression, and peritoneal dialysis can accelerate the recovery of pancreatitis and reduce the occurrence of serious complications. Patients with severe pancreatitis should not continue to use tamoxifen for endocrine therapy. If the situation allows, switching to a steroidal aromatase inhibitor is better to complete the follow-up endocrine therapy.